Knowledge Outcome of Helping Babies Breathe Training in Southern Nations, Nationalities and People’s Region, Ethiopia: A Pre- and Post-Test Study - Gamtessa LC; Kebede KM (Dove Medical Press, 2020)
Lalisa Chewaka Gamtessa,1 Kindie Mitiku Kebede2 1Department of Nursing, College of Health Sciences, Mizan-Tepi University, Mizan-Aman, Ethiopia; 2Department of Public Health, College of Health Sciences, Mizan-Tepi University, Mizan-Aman, EthiopiaCorrespondence: Lalisa Chewaka GamtessaMizan-Tepi University, Mizan-Aman, EthiopiaTel +251929334173Email lalisachewaka@gmail.comIntroduction: Helping Babies Breathe (HBB) training is a key strategy to decrease neonatal mortality. The objectives of this study were to evaluate the effect of HBB on knowledge outcome and to assess the knowledge outcome in relation to different variables in Southern Nations, Nationalities and People’s Region (SNNPR), Ethiopia.Methods: A pre- and post-test study was conducted using data from HBB trainings given for health workers. The training was given for 2.5 days and the knowledge outcome was evaluated using validated 18 questions. The post-test was given immediately after the training. Data were entered into Epi Info 7 and imported to SPSS version 21. The paired sample t-test was used to compare pre- and post-test means. The independent sample t-test was used to determine the relationship between knowledge outcome with sex, education level, and health facility. One way ANOVA with post hoc test was computed for comparing the knowledge outcome of the training among different professions. The general linear model (GLM) was used to determine the main and interaction effects. The statistical significance was determined at p< 0.05.Results: In this study, we assessed the knowledge outcome of 98 trainees. The trainees’ mean knowledge score increased from 64.4% (pre-test) to 80.7% (post-test). The difference was statistically significant with p< 0.001. Sex (pre-test p=0.003, post-test p=0.005) and education level (pre-test p=0.017, post-test p=0.037) of the trainees were significantly associated with the knowledge outcome while profession and type of health facility were not significant (p> 0.05). The GLM showed that the interaction effects of sex, education level, profession, and type of health facility over the knowledge outcome were non-significant (p> 0.05).Conclusion: The knowledge outcome of trainees significantly improved after the HBB training. It was significantly varied with sex and education level both at pre- and post-test. Therefore, these variables need consideration when arranging HBB trainings.Keywords: Helping Babies Breathe training, pre-test, post-test, knowledge outcome